THE FACT OF LEARNING ECONOMICS AT NATIONAL UNIVERSITY OF LAOS DURING THE PANDEMICS COVID-19 IN LAO PDR - Phousith Phongsavath; Agus Hermawan; Imam Mukhlis (Jurnal Pendidikan Humaniora, 2020)
Abstract: The out-breaking of Pandemics Covid-19 which is affected to many countries and regions in the world in the term of education. This study uses a qualitative approach which is the type of research is Phenomenology (case study). This type of phenomenological research is used due to it is oriented to the topic of teaching-learning economics course of teachers and students in National University of Laos. The determination of this research subject with the Snowball Sampling technique and the data collection techniques with in-depth interview and documentation. The finding results of this research found that learning economics in National University of Laos is not directly affected and is still continuing lecture as normal classes (face to face) and it is followed the order of National Operation Center for Covid-19 (NOCC) committee to resumed regular education after the extension of the annual yearly holiday during the Lao New Year in April 2020. For learning via online application, it has been already approved for teaching-learning for example: Google Meet, Zoom, skype etc. in addition, the perception and preparation most of them are readiness 100% which is mean that lecturers and students are aware of how to implement of online learning application.Keywords: pandemics, learning process, economics learning, higher education